ANALISIS FAKTOR â€“ FAKTOR YANG BERPENGARUH TERHADAP KESADARAN KEWAJIBAN PERPAJAKAN PADA SEKTOR USAHA KECIL DAN MENENGAH (UKM): (STUDY KASUS PADA USAHA KECIL DAN MENENGAH (UKM) DI LAMONGAN) - Mohammad Syafik; Rochman ÙÙÙArif (Media Mahardhika, 2020)
This study aimed to analyze the factors that influence the awareness of tax obligations on small and medium enterprises sector (SMEs) in the region of Lamongan, the factors examined in this study is the taxpayer's knowledge factor, the level of understanding of the sistem of self-assessment, the rate of income tax payers and influence the ease of payment sistem to the awareness of tax obligations on small and medium enterprise sector is arriving in the region of Lamongan.Samples of 48 respondents in Lamongan region. Data were collected through questionnaires, methods of data analysis using multiple linear regression analysis and data processing using computer program SPSS (Statistical Package For Social) version 21. Results from these studies show that the taxpayer knowledge factor, the level of understanding of the sistem of self assessment, the rate of income tax payers and influence the ease of payment sistems influence simultaneously to the awareness of tax obligations in the area of Lamongan, while the taxpayer knowledge factor, the level of understanding of the sistem of self assessment, influences the ease of sistem Payments significant influence, but of the three factors that affect the only factor related income level taxpayers negativ and not unidirectional.